Rare penetrant mutations confer severe risk of common diseases - Fiziev, Petko P; McRae, Jeremy; Ulirsch, Jacob C; Dron, Jacqueline S; Hamp, Tobias; Yang, Yanshen; Wainschtein, Pierrick; Ni, Zijian; Schraiber, Joshua G; Gao, Hong; Cable, Dylan; Field, Yair; et al. (Science (American Association for the Advancement of Science), 2023)
We examined 454,712 exomes for genes associated with a wide spectrum of complex traits and common diseases and observed that rare, penetrant mutations in genes implicated by genome-wide association studies confer ~10-fold larger effects than common variants in the same genes. Consequently, an individual at the phenotypic extreme and at the greatest risk for severe, early-onset disease is better identified by a few rare penetrant variants than by the collective action of many common variants with weak effects. By combining rare variants across phenotype-associated genes into a unified genetic risk model, we demonstrate superior portability across diverse global populations compared with common-variant polygenic risk scores, greatly improving the clinical utility of genetic-based risk prediction.